Newly-found channels in the interatrial septum of the heart by dissection, histologic evaluation, and three-dimensional microcomputed tomography. - Mi-Sun Hur; Seunggyu Lee; Chang-Seok Oh; Yeon Hyeon Choe (PLoS ONE, 2021)
A minute thrombus can pass through a small type of interatrial communication, which can result in a stroke or transient ischemic attack and several associated symptoms. This study sought to investigate a new type of interatrial communication. Thirty-one hearts from embalmed adult cadavers were investigated. Each interatrial channels (IACs) was classified as either an open or obstructed channel according to the connection of each hole on the right and left surfaces of the interatrial septum. Open channels were found in two specimens (6.5%). Both open and obstructed IACs followed tortuous courses through the interatrial septum. On the right surface of the interatrial septum, the hole was usually found adjacent to the left border of the interatrial septum between the opening of the superior vena cava into the right atrium and the superior margin of the fossa ovalis. Conversely, holes on the left surface of the interatrial septum were usually found in the upper and middle parts adjacent to the left border of the interatrial septum. This novel finding is expected to support our understanding of the onset of possible symptoms such as stroke in the absence of classical atrial septal defects.